Equilibrium and Kinetic Investigations of the Interaction of Model Platinum(II) Complex with DNA Constituents in Reference to the Antitumour Activity: Complex-Formation Reactions of [Pd(N,N-diethylethylenediamine)(H2O)2]2+ with Ligands of Biological Significance and Displacement Reactions of DNA Constituents - Eman Mohamed Shoukry (Bioinorganic Chemistry and Applications)
The [Pd(DEEN)Cl2] and [Pt(DEEN)Cl2] complexes were synthesized and characterized where DEEN=N,N-diethylethylenediamine. The stoichiometry and stability of the complexes formed between various biologically relevant ligands (amino acids, peptides, DNA constituents and dicarboxylic acids) and [Pd(DEEN)(H2O)2]2+ were investigated at 37∘C and 0.16 M ionic strength. The stability constant of the complexes formed in solution were determined and the binding centres of the ligands were assigned. The concentration distribution diagrams of the complexes were evaluated The equilibrium constants for the displacement of representative coordinated ligands such as inosine, glycine or methionine by cysteine were calculated and the concentration distribution diagrams of the various species were evaluated. The kinetics of base hydrolysis of free and coordinated S-methylcysteine methyl ester was investigated. The mechanism of hydrolysis was discussed.